PENGARUH WORD OF MOUTH, BRAND IMAGE, DAN PRODUCT KNOWLEDGE TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TANJUNGPURA PONTIANAK) - admin, NUR HIDAYAT B11112086 (Jurnal Manajemen Update, 2016)
Competition among manufacturers of smartphones is increasing, so companies always provide products that was updated to seize or retain customers. In this case the company should really pay attention to the image of products offered to consumers. So that consumers who were satisfied with the products bought gives positive word of mouth to other potential customers. In addition to provide complete information about the product is also very important, so that consumer knowledge about the product offered is more accurate. The number of brands of smartphones output china that offer cheaper prices and quality is almost the same, does not make Apple worry in the smartphone competition, because Apple through the iPhone smartphone has a good image in the eyes of consumers, so that consumers are more confident and feel safe to buy and use a smartphone iPhone. It is shown to be the iPhone smartphone market share increased by 35% in the second quarter of 2015. This study aimed to determine the effect of word of mouth, brand image and product knowledge to the purchasing decision smartphone iPhone by students of the Faculty of Economics and Business, University of Tanjongpura Pontianak. The sample in this study were 100 respondents drawn through the proportional method of random sampling and purposive sampling. In collecting the data obtained through questionnaires and measurement data through the Likert scale. Data analysis using validity, and reliabelitas, classic assumption test, regression test, t-test, f, and R determination test. Results achieved through SPSS 17 is known that word of mouth, brand image and product knowledge significantly influence purchasing decisions. With influences percentage of 18.3%. The remaining 81.7% is influenced by other variables not examined in this study. Keywords: Word of Mouth, Brand Image, Product Knowledge, Purchase Decision